NIGELLA SATIVA CONCOCTION INDUCED SUSTAINED SEROREVERSION IN HIV PATIENT - Onifade, Abdulfatah Adekunle; Jewell, Andrew Paul; Adedeji, Waheed Adeola (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
Nigella sativa had been documented to possess many therapeutic functions in medicine but the least expected is sero-reversion in HIV infection which is very rare despite extensive therapy with highly active anti-retroviral therapy (HAART). This case presentation is to highlight the complete recovery and sero-reversion of adult HIV patient after treatment with Nigella sativa concoction for the period of six months. The patient presented to the herbal therapist with history of chronic fever, diarrhoea, weight loss and multiple papular pruritic lesions of 3 months duration. Examination revealed moderate weight loss, and the laboratory tests of ELISA (Genscreen) and western blot (new blot 1 & 2) confirmed sero-positivity to HIV infection with pre-treatment viral (HIV-RNA) load and CD4 count of 27,000 copies/ml and CD4 count of 250 cells/ mm3 respectively. The patient was commenced on Nigella sativa concoction 10mls twice daily for 6 months.. He was contacted daily to monitor side-effects and drug efficacy. Fever, diarrhoea and multiple pruritic lesions disappeared on 5th, 7th and 20th day respectively on Nigella sativa therapy. The CD4 count decreased to 160 cells/ mm3 despite significant reduction in viral load (≤1000 copies/ml) on 30th day on N. sativa. Repeated EIA and Western blot tests on 187th day on Nigella sativa therapy was sero-negative. The post therapy CD4 count was 650cells/ mm3 with undetectable viral (HIV-RNA) load. Several repeats of the HIV tests remained sero-negative, aviraemia and normal CD4 count since 24 months without herbal therapy. This case report reflects the fact that there are possible therapeutic agents in Nigella sativa that may effectively control HIV infection.